A CONSTITUIÇÃO DOS ESPAÇOS LIVRES NA CIDADE DE ERECHIM-RS, RS, BRASIL E O PLANEJAMENTO DA PAISAGEM (Terr@ Plural, 2019)
This work aims to understand the constitution of Open Spaces in the city of Erechim, particularly those of public character, their relationship with urban morphology and its main agents of production. We analyzed overlapped maps and data in a GIS environment as well as qualitative and exploratory data. The research points out that there is disarticulation in the Open Spaces that emerged from land subdivision processes, and these Open Spaces do not have adequate infrastructure for social appropriation. It is also concluded that there is great potential to connect the Open Spaces studied with the railway line deactivated and thus a proposal is made to conform an Open Space System.